Toxicity against Artemia salina of the zoanthid Palythoa caribaeorum (Cnidaria: Anthozoa) used in folk medicine on the coast of Pernambuco, Brazil - Liany Figuerêdo de Andrade Melo; Claudio Augusto Gomes da Camara; Lourinalda Luiza Dantas da S. S. de Oliveira; Jeanne Claine de Albuquerque Modesto; Carlos Daniel Pérez (Biotemas)
Palythoa caribaeorum is a zoanthid whose mucus is traditionally used by fishermen communities on the southern coast of the state of Pernambuco as an anesthetic and anti-inflammatory agent, as well as for the treatment of topical wounds. In order to evaluate a possible toxicity, hexane and ethanol extracts of the zoanthid obtained from the beaches of Piedade (PCP-H; PCP-E), Guadalupe (PCG-H; PCG-E), and Suape (PCS-H; PCS-E) were tested against Artemia salina larvae. Among the six extracts tested, PCP-H, PCP-E, PCS-H, and PCS-E showed low toxicity, with LC50 values above 250µg/mL. On the other hand, PCG-H (80 < LC50 < 250µg/mL) was categorized as moderately toxic, while PCG-E (LC50 < 80µg/mL) was considered as highly toxic, with its degree of toxicity close to that of the standard drug cyclophosphamide (LC50 = 19.7µg/mL). The results indicate the presence of toxic compounds in the zoanthid obtained from Guadalupe and they suggest caution in the use of P. caribaeorum as a folk remedy. The variations found in the extracts of the tested Pernambucan populations of P. caribaeorum corroborate previous reports that the toxic action of this zoanthid is not inherent to the species, but it is influenced by environmental conditions and associated organisms.